Case report: Complete response of recurrent locally advanced basal cell carcinoma following addition of vismodegib to neoadjuvant cemiplimab therapy - Lambert-Swainston, Chalette; Samlowski, Wolfram; Reynolds, Brandon; Hedayat, Amin (Frontiers in Oncology, 2025)
Locally advanced basal cell carcinoma (laBCC) remains a significant management challenge. Historically, surgery or radiotherapy represented the major treatment options. Recently, hedgehog inhibitors and checkpoint inhibitors have demonstrated significant activity. The optimal sequencing of these approaches is not yet known. We describe a case of laBCC that recurred after definitive radiotherapy. This patient was treated with neoadjuvant cemiplimab with minimal response. Cautious addition of vismodegib with ongoing cemiplimab treatment was well tolerated and resulted in significant tumor regression. A wide excision demonstrated a pathologic complete response. Further evaluation of cemiplimab and hedgehog inhibitor combination therapy in la BCC appears warranted.